Active Surveillance for Prostate Cancer under the Patient Protection and Affordable Care Act. Issue 4 (July 2015) - Yuh, Lindsay; Dall'Era, Marc A.; Penson, David F.; Evans, Christopher P.
Abstract : Introduction: : Active surveillance is the standard alternative to immediate curative intervention in men with low risk prostate cancer. It avoids unnecessary treatments while allowing for curative intervention in cases that progress with time and it has added total cost savings without compromising outcomes compared to immediate treatment. Methods: : The 3 foci of the PPACA are to increase access to health care, improve quality of health care delivery and decrease costs. Results: : Multiple aspects of the PPACA are likely to impact the choice and delivery of active surveillance for prostate cancer management. Conclusions: : Programs including value based purchasing, episode based payments and accountable care organizations as well as increasing use of electronic health records may help promote the delivery of quality, efficient care for Americans. Active surveillance fits well in this model and becomes an attractive option for managing prostate cancer in the new health care environment.